Multidisciplinary Integration in Modern Management: A Systematic Review of Seven Strategic Perspectives - Muh. Haerdiansyah Syahnur; Atim Djazuli (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2025)
Background: The development of modern management and business science cannot be separated from interdisciplinary interactions and the complexity of global challenges. From classical management theories of the 1960s to the modern era of artificial intelligence (AI) and global crises, both academia and practitioners are increasingly required to adopt an integrative approach. Challenges in digital marketing, financial literacy, economic disruption, and human resource (HR) management demand the unification of diverse perspectives to build a more adaptive and relevant management framework. Objective: This article aims to summarize and synthesize findings from seven key scientific articles to present cross-issue perspectives and approaches that enrich contemporary management theory and practice. This synthesis is expected to identify new integrative patterns that can serve as a conceptual reference for the development of context-based and technology-driven management. Method: A descriptive qualitative approach was used in the form of a literature review of seven scientific articles from reputable international journals, covering topics such as management theory, digital marketing, financial behavior, responses to global crises, and HR systems. Results: The synthesis of the seven articles presented highlights the significant contributions of various management disciplines to modern management. This synthesis connects theory and practice, ranging from classical approaches like Koontz to cutting-edge technologies like AI in marketing. Furthermore, managerial approaches need to be tailored to actual situations and needs, such as in financial education, global policy, and HR management. Overall, this synthesis reflects the importance of cross-scale and cross-disciplinary perspectives—integrating aspects of psychology, technology, economics, and human resources—to form a more comprehensive management framework that is relevant to today's challenges. Conclusion: The synthesis of these seven articles demonstrates that modern management requires cross-disciplinary integration to address the challenges of the digital era, global crises, and organizational transformation. The resulting framework supports the need for management that is adaptive, contextual, and technology-based, while also affirming the importance of harmonizing theory, practice, and the dynamic realities of contemporary organizations.